The never war - MacHale, D. J. (MacHale, D. J. Pendragon, 2003)
Bobby and the Traveler from Cloral--Spader--have flumed to New York City, 1937. Against a backdrop of gangsters, swing music, and the distant sound of a brewing war, the two must uncover the evil Saint Dane's newest plot.